2019
DOI: 10.1002/aenm.201803612
|View full text |Cite
|
Sign up to set email alerts
|

Co–B Nanoflakes as Multifunctional Bridges in ZnCo2O4 Micro‐/Nanospheres for Superior Lithium Storage with Boosted Kinetics and Stability

Abstract: and vehicles. [1,2] With the ever-growing demand for the miniaturization of electrochemical energy storage devices, high volumetric lithium storage becomes more and more important. [3,4] Since conventional carbonaceous electrodes have approached the theoretical capacity limits, non-carbon alternatives with higher capacities are urgently required. [5] Transition metal oxides (TMOs) represent one type of promising alternative owing to their high specific capacities based on the conversion reaction mechanism, hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
66
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(68 citation statements)
references
References 65 publications
2
66
0
Order By: Relevance
“…Compared with the contribution curve (Figure S11a, Supporting Information) of Co‐Ni MOF, both diffusion and capacitive contributions of Co‐Ni‐B‐S are increased, which indicates that the electronic tuning by the redox treatment could enhance the ion diffusion abilities and capacitance simultaneously. For a better understanding of the enhanced performance of Co‐Ni‐B‐S, the capacitive‐ and diffusion‐controlled contributions in the samples of Co‐Ni MOF, Co‐Ni‐B, Co‐Ni‐S, and Co‐Ni‐B‐S are also calculated (Figure S11, Supporting Information) . It is evident that the increased scan rates enhance the proportion of capacitive contribution while the diffusion contribution proportion decrease, which is further proved by the irregular growth of CV curves (Figure S12, Supporting Information).…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Compared with the contribution curve (Figure S11a, Supporting Information) of Co‐Ni MOF, both diffusion and capacitive contributions of Co‐Ni‐B‐S are increased, which indicates that the electronic tuning by the redox treatment could enhance the ion diffusion abilities and capacitance simultaneously. For a better understanding of the enhanced performance of Co‐Ni‐B‐S, the capacitive‐ and diffusion‐controlled contributions in the samples of Co‐Ni MOF, Co‐Ni‐B, Co‐Ni‐S, and Co‐Ni‐B‐S are also calculated (Figure S11, Supporting Information) . It is evident that the increased scan rates enhance the proportion of capacitive contribution while the diffusion contribution proportion decrease, which is further proved by the irregular growth of CV curves (Figure S12, Supporting Information).…”
mentioning
confidence: 92%
“…Moreover, the O 1s XPS profiles of Co‐Ni MOF and Co‐Ni‐B‐S can be deconvoluted into three distinct peaks (Figure f), which can be classified as lattice oxygen (O I , ≈531.1 eV), oxygen vacancies (O II , ≈531.8 eV), and chemisorbed or dissociated oxygen or OH species (O III , ≈533.4 eV) . Compared with the Co‐Ni MOF, the O II peak intensity in the Co‐Ni‐B‐S sample increases significantly, which implies the introduction of oxygen vacancies in the redox process . The loss of oxygen could produce a large number of positive holes and defects, which are beneficial for the electrons transfer.…”
mentioning
confidence: 99%
“…The specific capacities of EA and TA LIBs can be comparable with those of metal oxide LIBs after cycling, and the cycling stabilities of EA and TA LIBs are better than those of metal oxide LIBs. [13,[52][53][54] The exceptional electrochemical performance of EA and TA indicates that they are promising anode materials for LIBs.…”
Section: Resultsmentioning
confidence: 99%
“…There have been several approaches in the literature aimed at minimizing the effects of these MO degradation mechanisms. Many authors have created highly tailored architectures including anchored-materials, 44 shelled-materials (e.g. singleshell, [45][46][47][48] yolk-shell, 49,50 multi-shell [51][52][53] ), and hierarchical frameworks.…”
Section: Introductionmentioning
confidence: 99%
“…singleshell, [45][46][47][48] yolk-shell, 49,50 multi-shell [51][52][53] ), and hierarchical frameworks. [54][55][56] For instance, Deng et al 44 have demonstrated that ZnCo 2 O 4 with cobalt-boride (Co-B) anchors can reduce degradation, volume change and phase segregation. This is accomplished by utilizing Co-B as an intra-particle "glue" that promotes enhanced intra-particle electron conduction and faster Li + diffusion to/from the ZnCo 2 O 4 structure.…”
Section: Introductionmentioning
confidence: 99%